Gamma irradiation of PVdF based polymer electrolytes - Ayoub, N.; Amin, Y.M.; Arof, Abdul Kariem (2009)
Solutions of PVdF containing various concentration of LiPF 6 were gamma irradiated. The solutions were then cast to form films. The conductivity of the solid polymer electrolyte was then determined by electrochemical impedance spectroscopy (ElS). Dielectric properties of the solid polymer electrolyte were also discussed.